2003
DOI: 10.1191/0961203303lu405oa
|View full text |Cite
|
Sign up to set email alerts
|

The effects of antiphospholipid antibodies obtained from women with SLE/APS and associated pregnancy loss on rat embryos and placental explants in culture

Abstract: Recurrent fetal loss occurs in approximately 1% of women. Autoimmune causes have been suggested as a factor in some of these cases. High rates of intrauterine fetal growth retardation and increased incidence of prematurity is associated with systemic lupus erythematosus (SLE) and the antiphospholipid syndrome (APS). We found in previous studies that sera from SLE/APS patients when used as a culture medium for rat embryos were found to reduce embryonic growth and development, induce a high rate of embryonic ano… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
48
1
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(52 citation statements)
references
References 21 publications
2
48
1
1
Order By: Relevance
“…It has actually been reported that aPL binding to trophoblasts might end into direct cellular injury, apoptosis, inhibition of proliferation and syncytia formation, decreased human chorionic gonadotrophin (hCG) production and defective invasiveness [15][16][17][18]. Al these aPL-mediated effects might cause a defective placentation.…”
Section: Defective Placentationmentioning
confidence: 99%
“…It has actually been reported that aPL binding to trophoblasts might end into direct cellular injury, apoptosis, inhibition of proliferation and syncytia formation, decreased human chorionic gonadotrophin (hCG) production and defective invasiveness [15][16][17][18]. Al these aPL-mediated effects might cause a defective placentation.…”
Section: Defective Placentationmentioning
confidence: 99%
“…The majority of studies have examined the effects of polyclonal aPL isolated from patient sera, as well as murine monoclonal aPL on placental explants or cell lines (Yacobi et al 2002, Ornoy et al 2003, Bose et al 2004, Schwartz et al 2007. Studies examining the mechanism of reduced migration showed that aPL mediate this effect possibly through the downregulation of interleukin 6 (IL6; Mulla et al 2010) and the up-reguation of TIMP2 (Albert et al 2014), all independently of Toll-like receptor 4 (TLR4).…”
Section: Trophoblast Proliferation Migration and Invasionmentioning
confidence: 99%
“…Several in vitro studies have reported an increase in trophoblast death in response to aPL using either term trophoblasts or first-trimester trophoblasts (Di Simone et al 2001, Yacobi et al 2002, Ornoy et al 2003, Schwartz et al 2007, Chen et al 2009, Mulla et al 2009). Cytotrophoblasts isolated from term placentae (Di Simone et al 2001 have been shown to alter their expression of the apoptotic regulators Bax and Bcl2 in response to aPL, but without overt signs of cell death (Di Simone et al 2006).…”
Section: Trophoblast Deathmentioning
confidence: 99%
“…The embryos were cultured in Dulbecco's Modified Eagle's Medium (DMEM)/F12 and 20% fetal calf serum (Ornoy et al, 2003a) in the presence of IgG and specific aPLA purified from SLE/APS patients with RPL, which were added to the culture medium in the same concentrations as in the original sera (Matalon et al, 2002;Ornoy et al, 2003b). At that stage, many of the embryonic organs have already been formed; therefore, it is expected that the main effects (if any at all) will be on embryonic growth and viability (Matalon et al, 2002).…”
Section: Rat Embryos and Human Placental Explants: Useful Culture Sysmentioning
confidence: 99%
“…Therefore, studies were undertaken to examine the effects of sera from SLE/APS patients on early human placental explants obtained from interruptions of normal 5.5-to 7.5-week-old pregnancies, as compared to the effects of sera from healthy women and of the chemically defined medium in general use for placental culture, F-12/Ham's medium (Genbacev et al, 1992;Ornoy et al, 2003b;Yacobi et al, 2002).…”
Section: Rat Embryos and Human Placental Explants: Useful Culture Sysmentioning
confidence: 99%